Crash course in public library administration - Disher, Wayne (Santa Barbara, Calif. Libraries Unlimited, 2010)
"This book is intended to present a quick and informative look at public administration principles and how they are often applied in public institutions, particularly the public library environment"--P. xi.
Local government and its services -- Public administrators -- The design of an organization -- Power and politics in organizations -- Budgeting -- Planning -- Human resources and personnel -- Communicating in the public realm -- Councils, boards, and commissions -- Working in teams -- Solving problems and making decisions -- Facilities management -- Knowing the community -- Public policies -- Implementing organizational change.
Keywords: Public libraries -- United States -- Administration